Does the outcome of diagnostic ultrasound influence the treatment modalities and recovery in patients with shoulder pain in physiotherapy practice? Results from a prospective cohort study. (June 2019) - Karel, Yasmaine Helga Jacques Marie; Miranda, Audilia; Thoomes-de Graaf, Marloes; Scholten-Peeters, Gwendolijne GM.; Ottenheijm, Ramon PG.; Koes, Bart W.; Verhagen, Arianne P.
Abstract: Study design: Prospective cohort study including patients with shoulder pain in primary care physiotherapy. Background: There is an increased tendency to use diagnostic ultrasound to aid the diagnostic strategy and target treatment. It is a relatively cheap and accessible imaging technique but the implications for practice and patients are unknown. Objectives: To study the influence of diagnostic ultrasound (DUS) on diagnostic work-up, treatment modalities and recovery. Methods: Participants (n = 389) with a new episode of shoulder pain were assessed at baseline and followed for 6, 12 and 26 weeks. Diagnostic work-up, including the use of DUS, and treatment strategies were reported by the therapists at 3, 6 and 12 weeks. Results: Most patients (41%) were diagnosed with subacromial impingement/pain syndrome after physical examination or DUS. DUS was used in 31% of the participants. Tendinopathy was the most found abnormality in this sub-population. Patients who underwent DUS were more frequently treated using exercise therapy. Patients that not had DUS were more likely to receive massage therapy, trigger point therapy or mobilisation techniques. Logistic regression analyses did not show a significant association between DUS and recovery after 26 weeks (0.88, 95%CI:0.50–1.57). Correcting for the therapist as a confounder using a multilevel binary logistic regression did not show a significant cluster effect. Conclusion: Diagnostic US as a work-up component does not seem to influence diagnosis or recovery but does influence the choice of treatment modality. Conclusions are limited to observational data. High quality randomized trials should study the effect of DUS on recovery. Highlights: About one third of patients received a diagnostic ultrasound. Tendinopathy was the most observed abnormality, followed by calcification. Diagnostic ultrasound does not seem to influence diagnostic work-up, and recovery. The choice of treatment slightly differed between the ultrasound groups. Advise was the most common treatment approach regardless of clinical diagnosis.